Priors of voting repetition intention for the same politician - de Oliveira, Victor Ricardo (2020)
This study aimed to identify the influence that loyalty, interest in benefits, satisfaction and confidence in the politician have on the intention of the voter to repeat the vote in the same politician. A theoretical model was developed with the constructs in question, analogously contextualized in the marketing of products and services. After the questionnaire was completed and the data collected, the final sample consisted of 522 respondents. Data analysis was carried out by modeling structural equations and the results showed that confidence, satisfaction and interest in benefits positively and directly influence voter loyalty, thus establishing an indirect antecedent of the intention to repeat voting, given the loyalty positively and directly influences that intention. It is concluded that the intention to vote in a same politician pervades several behavioral elements of the voter, forming his loyalty to the politician in reelection.